2014
DOI: 10.1002/ijc.29371
|View full text |Cite
|
Sign up to set email alerts
|

Late psychiatric morbidity in survivors of cancer at a young age: A nationwide registry‐based study

Abstract: Childhood cancer survivors have been shown to be prone to psychosocial adverse outcomes. Data on young adults and their psychiatric late effects are still scarce. In a nationwide, registry-based study, we explored the risk (HR) of new psychiatric diagnoses in 5-year survivors of childhood and young adulthood (YA) cancer (n 5 13,860) compared with a sibling cohort (n 5 43,392). Hazard ratios (HRs) were calculated using Cox regression models. Patients and siblings were identified from the Finnish Cancer Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 42 publications
9
58
2
1
Order By: Relevance
“…More specifically, with respect to the Total problem scale and to the summary scales, the variables female gender, related allogeneic HSCT, acute and long-term sequelae, psychophysical problems, and time elapsed between the communication of the need to transplant and the effective transplantation were shown to be predictors of a higher risk of experiencing psychopathology. These results are in line with the literature that identifies females at a higher risk of developing psychopathological problems subsequent to oncologic disease and transplantation (Ahomäki et al, 2015). Furthermore, allogeneic related transplantation was shown to be a risk factor for experiencing a higher degree of emotional and behavioral difficulties, in accordance with other studies that already identified children undergoing autologous transplant as less likely to experience significant somatic distress and impairments when compared with those exposed to allogeneic intervention, both related or unrelated (Phipps et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…More specifically, with respect to the Total problem scale and to the summary scales, the variables female gender, related allogeneic HSCT, acute and long-term sequelae, psychophysical problems, and time elapsed between the communication of the need to transplant and the effective transplantation were shown to be predictors of a higher risk of experiencing psychopathology. These results are in line with the literature that identifies females at a higher risk of developing psychopathological problems subsequent to oncologic disease and transplantation (Ahomäki et al, 2015). Furthermore, allogeneic related transplantation was shown to be a risk factor for experiencing a higher degree of emotional and behavioral difficulties, in accordance with other studies that already identified children undergoing autologous transplant as less likely to experience significant somatic distress and impairments when compared with those exposed to allogeneic intervention, both related or unrelated (Phipps et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible to speculate as to whether HSCT survivors could experience anticipatory fear linked to their previous traumatic experience and express it through worries about physical well-being, a hypothesis that could in part explain the parallel presence of high scores on somatic symptoms and low scores on post-traumatic stress symptoms (Bingen et al, 2012; Ahomäki et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 A Danish study reported an increased risk of hospital contacts for mental disorders in childhood cancer survivors when compared with population-based comparisons. 8 Suicides, alcohol and drug abuse, accidents, and violence as causes of death can be regarded as an extreme manifestation of risky health behavior. 8 Suicides, alcohol and drug abuse, accidents, and violence as causes of death can be regarded as an extreme manifestation of risky health behavior.…”
Section: Introductionmentioning
confidence: 99%